การสร้างแบรนด์ห้องสมุดมหาวิทยาลัย - ชัยช่วย วิศปัตย์ (Journal of Information Science Research and Practice, 2013)
บทคัดย่อ ในปัจจุบันห้องสมุดมหาวิทยาลัยต้องเผชิญกับความเปลี่ยนแปลงหลายประการ โดยเฉพาะปริมาณผู้ใช้ที่ลดลง และการประเมินคุณภาพที่เข้มข้นมากขึ้น เพื่อรับมือกับการเปลี่ยนแปลงดังกล่าว ห้องสมุดหลายแห่งได้ให้ความสำคัญกับการสร้างแบรนด์ เพื่อสร้างชื่อเสียงและการยอมรับจากผู้รับบริการ สำหรับบทความนี้กล่าวถึงการสร้างแบรนด์ ซึ่งเป็นแนวคิดเชิงการตลาดและการบริหารองค์กรสมัยใหม่ โดยจะให้มุมมองบางประการในการสร้างแบรนด์ห้องสมุดมหาวิทยาลัย คำสำคัญ: การสร้างแบรนด์; การตลาด; ห้องสมุดมหาวิทยาลัย Abstract Nowadays, university library faces the numerous changes, especially the decrease ofusers and intensive quality assessment. In order to prepare for the upcoming situation, most of libraries putmuch emphasis on branding development to create their reputation and well user perspective. This articledescribes branding development concept, which are related to marketing concept and modern organizationmanagement, to provide some perspective on university library branding. Keywords: Branding; Marketing; University Library